Analysis of Quality Performance of We3000 Power Plant of Window Power Station - Maktuba Rakhmatova; G’ofur Rakhmatov (Research Parks Publishing LLC, 2022)
This article provides information on models for providing quality indicators of voltage through reactive power coverage in wind power plants.